Analisis Islamic Corporate Governance dan Islamic Intellectual Capital terhadap Profitabilitas BUS di Indonesia - Hani Anisa Rinjani; Kusnendi; Cakhyaneu, Aneu (Jurnal Ekonomika dan Bisnis Islam, 2022)
The development of the profitability of Islamic banks is still lower than that of conventional banks, so it is necessary to identify related strategies that must be applied to increase profitability, especially profits from asset management. This study aims to analyze the effect of Islamic Corporate Governance and Islamic Intellectual Capital on the Profitability of Islamic Commercial Banks in Indonesia. The population in this study includes all Islamic Commercial Banks in Indonesia. The sample used consists of eleven Islamic Commercial Banks in Indonesia for the 2016-2020 period. The research method used is quantitative with a descriptive causality research design. The data analysis technique in this study is the panel data regression method. The results of this study indicate that Islamic Corporate Governance has a negative effect on the profitability of Islamic Commercial Banks in Indonesia. Furthermore, Islamic Intellectual Capital has a significant positive effect on the profitability of Islamic Commercial Banks in Indonesia. This study implies that Islamic banking in carrying out its operational performance needs to pay attention to the quality of human resources, capital and systems including supporting technology and work culture that is applied as an effort to increase profitability.